Olivia Bitter, spooked-out sitter - Gunderson, Jessica (North Mankato, Minnesota Capstone Press, 2016)
When thirteen-year-old Olivia is asked by her new neighbors to babysit their four kids for the weekend, she is a little apprehensive because their house is supposed to be haunted, but she also thinks it may be a way to win back her best friend who has started hanging out with the "in" girls
A gift from book Africa
Horror & Ghost stories
1 2 13 15
NEW_ZTN_GN
Keywords: Haunted houses -- Juvenile fiction; Babysitting -- Juvenile fiction